(untitled) (Hoboken, N.J, 2005)
The editors and the chapter authors of this book are to be applauded for providing biologists with lucid and comprehensive descriptions of essential topics in bioinformatics. This book is easy to read, highly informative, and certainly timely. It is most highly recommended for students and for established investigators alike, for anyone who needs to know how to access and use the information derived in and from genomic sequencing projects."
Keywords: Bioinformatics.,Computational Biology,Cấu trúc phân tử; Methods